Systematic Literature Review: Evaluasi Kebijakan Program Bantuan.Pangan Non-Tunai (BPNT) Berdasarkan Model William N Dunn (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2026)
Non-Cash Food Assistance (BPNT) is a government assistance program aimed at poor or underprivileged communities, distributed monthly through electronic accounts and used specifically to purchase basic necessities at designated E-Warong stores. However, in reality, the implementation of the BPNT program in the field still faces comprehensive challenges, such as issues related to targeting inaccuracy and the quality of food obtained by KPM not always meeting standards. The purpose of this study is to explore the evaluation of the Non-Cash Food Assistance (BPNT) program policy through a Systematic Literature Review (SLR) approach, so that researchers can trace various empirical findings regarding the implementation of the Non-Cash Food Assistance program policy in several regions. The policy evaluation model used is William N Dunn's model, which includes six indicators, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results of this study are expected to provide a comprehensive and in-depth picture of the phenomenon being studied in an objective and systematic manner, and can be used as a reference for government agencies in evaluating and optimizing the implementation of the BPNT program policy so that it becomes a more effective and sustainable social assistance program.